Preservasi pengetahuan lokal mitos di Dusun Kasuran Seyegan Sleman Daerah Istimewa Yogyakarta - Baroroh, Wasilatul (Berkala Ilmu Perpustakaan dan Informasi, 2024)
Introduction. This study aims to identify efforts to preserve local mythological knowledge in Kasuran Hamlet through exchange of indigenous knowledge, so that local knowledge exists. Data Collection Methods. The research employs a qualitative method.Data collection involves interviews, observations, and literature reviews. Data Analysis. The data analysis technique uses the exchange of indigenous knowledge model. The stages of data analysis include data reduction, analysis, and conclusion. Results and Discussion. Kasuran Hamlet has a unique myth, which is the prohibition of sleeping on a mattress. The community believes that they will get misfortune if they violate the taboo. The preservation of this myth is carried out through the exchange of indigenous knowledge, including: 1) recognizing and identifying myths; 2) validating the authenticity and distinctiveness of myths; 3) recording and documentation as information products; 4) storage for easy access; 5) transfer of knowledge; and 6) dissemination of knowledge to individuals and communities. Conclusion. The efforts to preserve local mythological knowledge in Dusun Kasuran through exchange of indigenous knowledge have effectively maintained local traditions. The involvement of the community, government, and researchers strengthens the existence of myths in Kasuran Hamlet as an identity and cultural heritage.